An Examination of Technology Acceptance Models for Chatbot Adoption in Startup E-businesses: A Narrative Review - Ali Najarian; Roya Hejazinia (International Journal of Management, Accounting and Economics)
Incorporating chatbots into the framework of emerging businesses is a pivotal strategy for augmenting procedural efficacy and fostering customer involvement. Chatbots liberate resources by automating customer dialogues and refining processes, enabling them to concentrate on tasks of higher importance. Furthermore, chatbots offer a personalized and captivating customer journey, which can be instrumental in cultivating trust and allegiance. The study aims to investigate the theories that support using chatbots in startup businesses. We used a narrative review method on" ScienceDirect, Web of Science, and Scopus" databases with the keywords "acceptance model, chatbot, startups, artificial intelligence, e-business or e-commerce" between 2020 and 2024 to analyze well-known theories. After 176 studies, 20 were chosen for in-depth analysis. Moreover, our findings included TRA, TPB, TAM, ETAM, IM, SCT, DOI, PCIT, MM, U&G, MPCU, UTAT, and C_UTAT. The findings reveal that TAM is the most widely used theory among the examined ones, indicating its effectiveness in guiding startups toward successful chatbot adoption strategies. This study adds value to the existing literature by providing insights into the theoretical frameworks that drive chatbot adoption in the startup community.